HTX-019 via 2-min injection or 30-min infusion in healthy subjects. (21st December 2018) - Ottoboni, Thomas; Lauw, Michael; Keller, Mary Rose; Cravets, Matt; Manhard, Kimberly; Clendeninn, Neil; Quart, Barry
Aim: HTX-019 (CINVANTI ® [aprepitant injectable emulsion]) is a neurokinin 1 receptor antagonist approved for preventing acute and delayed chemotherapy-induced nausea and vomiting (CINV). HTX-019 is free of polysorbate 80 and other synthetic surfactants and showed bioequivalence to and a more favorable safety profile than fosaprepitant when administered as a 30-min infusion in healthy subjects. The shortage of small-volume parenteral solutions led to a recommendation to administer HTX-019 by intravenous push. The objectives were to evaluate pharmacokinetics, tolerability and safety following HTX-019 administration by injection versus infusion.Materials & methods: Study comprised Part A, a pilot Phase I, single-center, randomized, pharmacokinetic, safety and tolerability, open-label study, followed by Part B, a two-sequence crossover study of HTX-019 130 mg in healthy adults, via injection and infusion. Blood samples were evaluated for aprepitant pharmacokinetics and bioequivalence. Safety evaluations included treatment-emergent adverse events (TEAEs), vital signs, clinical laboratory testing and electrocardiograms.Results: In Part A, 24 subjects were randomly assigned to three cohorts (n = 8 per cohort) and received HTX-019 130 mg, administered intravenously over 15 min (cohort 1), 5 min (cohort 2) or 2 min (cohort 3). Progression to Part B occurred after acceptable tolerability was established in cohorts 2 and 3. In Part B, 50 randomized subjects received a 2-min injection (9 ml/min) and 30-min infusion (296 ml/h) of HTX-019 130 mg. Bioequivalence was demonstrated for HTX-019 injection and infusion. Both administration methods via a peripheral line were well tolerated; eight subjects experienced 11 TEAEs (six related) following injection and nine experienced 14 TEAEs (nine related) following infusion. Headache and fatigue were the most prevalent treatment-related TEAEs; one subject per group experienced feeling hot ≤30 min after drug administration.Conclusion: Pharmacokinetic and tolerability profiles of 2-min HTX-019 injection support this potential alternative administration method for CINV prevention. Lay abstract: This study assesses the management of a common side effect of chemotherapy, known as chemotherapy-induced nausea and vomiting (CINV), and addresses a major shortage of small-volume solutions and intravenous bags used to deliver treatment to prevent CINV. Although effective treatments to prevent CINV are available, a high percentage of patients with cancer receiving chemotherapy still experience this side effect. HTX-019, an injectable emulsion of aprepitant, was approved in 2017 as a 30-min infusion to prevent CINV associated with chemotherapy. In November 2017, US FDA announced a shortage of small-volume parenteral solutions, including those used in administering HTX-019. The American Society of Health-System Pharmacists recommended switching the delivery of treatments by infusion to iv. push (injection over 5 min or less) whenever possible. In this study, HTX-019 130 mg given as a 2-min injection was comparable in effectiveness and safety to the 30-min infusion, and both methods of administration were well tolerated. These findings confirm the short injection as an alternative method of administering HTX-019 to prevent CINV, reducing the need for iv. bags.